Evaluation of Resistance to Conventional Antibiotics in Medicine by 5 Strains of Lactic Acid Bacteria Isolated from the Stomach of Honey Bee - Gharehyakheh, Sepideh; HosseinElhamirad, Amir; Nateghi, Leila; Varmira, Kambiz (Asian Journal of Biological and Life Sciences, 2017)
This study describes the sensitivity of bacteria isolated from the stomach of the honey bee to conventional antibiotics in medicine. The bacteria include Lactobacillus pentosus (HM027640), Lactobacillus sp. Taj Naser-1 (GQ451611), Lactobacillus fermentum (HM027642), Lactobacillus kunkeei (GQ451631), and Lactobacillus sp. Makhdzir Naser-1 (GQ451633) isolated from the honey stomach of the honey bee. The disk diffusion method was used in this study. Lactobacillus pentosus (HM027640) exhibited the highest sensitivity to amoxicillin (30 μg), kanamycin (30μg), and streptomycin(10µg); Lactobacillus kunkeei (GQ451631) to ampicillin (10 μg); Lactobacillus sp. Makhdzir Naser-1 (GQ451633) to chloramphenicol (30 µg) and penicillin (10µg) and Lactobacillus sp. Taj Naser-1 (GQ451611) to erythromycin (15 µg). The highest resistance to amoxicillin (30µg) was exhibited by Lactobacillus fermentum (HM027642); against kanamycin (30 μg) and ampicillin (10μg) by Lactobacillus sp. Taj Naser-1 (GQ451611), against chloramphenicol (30 µg), and streptomycin(10µg) Lactobacillus kunkeei (GQ451631), and against erythromycin (15 µg) and penicillin (10 µg) by Lactobacillus pentosus (HM027640). The impact of antibiotic type on the resistance of lactic acid bacteria was quite effective. In some bacteria, resistance to several antibiotics was observed; however, this was not problematic, because the diameter of the inhibitory zone was much larger than standard.
Keywords: Antibiotic; Disk diffusion; Honey stomach; Lactic acid bacteria; Resistance; the diameter of inhibitory zone